TELAAH ISLAM ATAS PERKEMBANGAN MORAL MANUSIA MENURUT THOMAS LICKONA - Khuzie Sahala Hidayah; Septi Gumiandari (CV. ADIBA AISHA AMIRA, 2025)
Lawrence Kohlberg brought a theory of moral development based on moral reasoning which is a product of ratio or reason. The author tries to raise the perspective of Islamic education. The method used by the author is qualitative and library research with documentary research sources based on moral development theory and Islamic theory. Lawrence Kohlberg's moral development theory discusses the development experienced by humans who will reach a certain stage of development by going through the previous moral stages. This paper reveals the perspective of Islamic education on Lawrence Kohlberg's moral development theory. This research produces, first, the theory of moral development based on anthropocentric and theocentric, second, the common thread between spiritual intelligence and religion called spiritual intelligence, which must be possessed by students as a condition for becoming moral human beings. (Kuswandi, 2020)